Idea wyodrębnienia dyscypliny naukowej „nauki o bezpieczeństwie” i jej konsekwencje - Lutostański, Marian (Historia i Polityka, 2018)
There are numerous controversies regarding the fields of study of “security”. Reported objections are represented in the context of “nationalization” and another field of study – “defense studies”. The study is an attempt to answer two questions: 1) what is the rationale to contest the current list of areas of academic study, academic disciplines and fields of study in the area of security and defense studies?; 2) what are the possible solutions to remove controversial issues in that classification? The article also provides a short reflection on the “security engineering” as an autonomous discipline. In the final part of the foregoing shows the original model solutions of an existing problem.